2019
DOI: 10.1080/19336950.2019.1631106
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of TRPV1 in pulmonary hypertension: Angel or demon?

Abstract: Pulmonary hypertension (PH) is a pathological state defined by increased pulmonary artery pressure, the pathogenesis of which is related to genetic mutations, intracellular calcium ([Ca 2+ ] i), inflammation and proliferation. Transient receptor potential vanilloid subfamily member 1 (TRPV1) is a nonselective cation channel expressed in neural and nonneural cells, including pulmonary vessels and nerves. As a calcium channel, TRPV1 can make vessels contracted, and promote smooth muscle cells proliferation throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Studies with animal models of common vascular diseases, like systemic and pulmonary hypertension, atherosclerosis and restenosis, which use KO mice of different TRP isoforms, suggest the translational potential role of TRPC and TRPV channels. Previous cutting-edge studies have suggested that these channels might be major regulators of cellular remodeling through their ability to modulate transcriptional programs that drive cell proliferation and migration, and even cytokine secretion [ 18 , 70 , 92 ]. As reviewed above, there is general agreement that most isoforms of TRPCs are implicated in cellular remodeling, a critical step for vascular disease progression, which occurs in systemic and pulmonary hypertension, atherosclerosis and restenosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies with animal models of common vascular diseases, like systemic and pulmonary hypertension, atherosclerosis and restenosis, which use KO mice of different TRP isoforms, suggest the translational potential role of TRPC and TRPV channels. Previous cutting-edge studies have suggested that these channels might be major regulators of cellular remodeling through their ability to modulate transcriptional programs that drive cell proliferation and migration, and even cytokine secretion [ 18 , 70 , 92 ]. As reviewed above, there is general agreement that most isoforms of TRPCs are implicated in cellular remodeling, a critical step for vascular disease progression, which occurs in systemic and pulmonary hypertension, atherosclerosis and restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, TRPV1, V3 or V4 likely play a protective role in systemic hypertension and atherosclerosis, since they participate in NO release via endothelium and metabolism lipid regulation [ 87 , 101 , 108 , 109 ]. In contrast, TRPV1 and V4 activation seem critical for hypoxia-induced Ca 2+ increase and further PASMCs proliferation and migration [ 92 , 117 ]. Nevertheless, future studies are urgently needed to address the downstream targets and mechanisms modulated by these channels, as well as the upstream regulators leading to changes in their expression and function during disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al [ 71 ] suggested that, on the one hand, TRPV1 induces an increase in intracellular calcium ([Ca 2+ ] i ) in PASMCs and can cause vascular contractions, as well as promoting smooth muscle cell proliferation, which can lead to PH. On the other hand, the activation of TRPV1 in sensory nerves can release neuropeptides, including the calcitonin-gene-related peptide (CGRP) [ 71 ]. CGRP causes the relaxation of blood vessels and inhibits their proliferation, which may be beneficial in PH [ 71 ].…”
Section: Receptor-mediated Vasodilatationmentioning
confidence: 99%